ENHANCING MSME EMPOWERMENT THROUGH TECHNOLOGY ADOPTION: A UNIVERSITY-INDUSTRY PARTNERSHIP - Setiadi, Nugroho J.; Prasandy, Teguh; Alam, Doni P. (Bina Nusantara University, 2024)
This community service initiative focuses on universities' integration of science, technology, and expertise with Micro, Small, and Medium Enterprises (MSME) partners. The program, part of the Partnership for Knowledge Management (PkM) framework, is designed to directly benefit economically productive micro-businesses, primarily in the fashion creative industry subsector, within Bandung city and district. The initiative involves the implementation of digital business simulations and mentoring for local MSMEs. A central component of this effort is a digital application that provides a visual dashboard illustrating market competition based on specific product attributes. This Decision Support System (DSS) assists MSME decision-makers. The collaboration includes Binus University, Mocaca.id, an e-commerce trading platform, and multiple local MSMEs in Bandung, West Java. The initiative's primary goal is to enhance MSME partner empowerment in the competitive business landscape. The project engaged four lecturers and four student interns, contributing to both research and program application development. Beyond its direct impact on businesses, this initiative benefits students and educators while advancing university key performance indicators, particularly in student internships, curriculum enrichment, research output, and institutional recognition (IKU 2, 5, 6, and 7). This partnership underscores the vital role of universities in supporting MSME innovation and competitiveness.